Approaching nakedness and its problematics : a 1-1 (one with one) performance about being naked in an intimate platonic way - Konnaris, Petros (My University, 2017)
Nakedness can mean not wearing any clothes but it could also mean not having your socks on. I see nakedness as a social construct that can shift meanings depending on the context, the culture and the subject(s) being or not being naked. In Approaching Nakedness and Its Problematics I use personal experiences I had in Europe and Thailand, the words Naked, Nude and Τίτσιρος (:Titsiros), borrow ideas from Donna Haraway, the trans philosopher Talia Mae Bettcher, and the indigenous scholar Irene Watson to introduce the multiplicity of nakedness. I present some of the problematics of nakedness such as objectification, male gaze, exhibitionism and voyeurism, toxic masculinity, gender binaries, and normalized body images. Afterward, I present queer and feminist theories of Judith Butler, Diane Ponterotto, and Talia Mae Bettcher on how to resist those problematics. I then contextualize my work in relation to other artists, their work and the mentioned problematics. I continue with my artistic project A Bathing Performance, a 1-1(one with one) happening of nakedness and care, presenting my methodology, my aims, my reflections and observation. In the project, I limit the spectrum of nakedness and focus on nakedness as an intimate, platonic act. Additionally, I introduce the term one with one and explore performance as a meeting, a mutual, interconnected exchange with another person. I approach both nakedness and the performance as a multiplicity, a range of options and choices that one can decide how, when and where he/she/they want to experience nakedness. The written part of my thesis includes an academic text and a handwritten book: a replica of the scorebook I used in the performances in June 2017 which includes the updated version of my 30 bathing scores/proposals.
Keywords: 1-1(one with one) performance; queer; bathing scores; multiplicity; Nakedness.; Performance art.; Intimacy.; Platonism.; Feminism.; Live art.; Diversity.; alastomuus; performanssi; läheisyys; feminismi; esitystaide; monimuotoisuus; nakenhet; performance; närhet; feminism; diversitet; LAPS